Analisis Tingkat Aktivitas Fisik Siswa SMA Muhamadiyah 1 Palangka Raya - Syahrullah, Adi; Mikdar, Ujen Zenal; Wahyudi, Arief Nur; Gressia, Gressia; Nur'aeni, Nur'aeni (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the level of physical activity among students of SMA Muhammadiyah 1 Palangka Raya and to identify gender-based differences in physical activity. A quantitative approach with a descriptive survey design was used. The sample consisted of 60 students selected using cluster sampling technique. The instrument employed was the Global Physical Activity Questionnaire (GPAQ), which generates MET (Metabolic Equivalent of Task) scores as indicators of physical activity intensity. Data were analyzed descriptively and inferentially using an independent t-test. The results showed that the average MET score was 3875.54, indicating a high level of physical activity. Specifically, male students had a higher mean MET score (M = 4801.93) than female students (M = 3004.68). The t-test revealed a statistically significant difference between the two groups (p = 0.014). These findings highlight a gender gap in physical activity, potentially influenced by biological, social, and environmental factors. The study recommends implementing school-based interventions that promote equal participation in physical activities to support students’ overall health and physical fitness.